Complementary medicine and primary dysmenorrhea - Ataollahi, Maryam; Amir AliAkbari, Sedigheh (Advances in Nursing & Midwifery, 2014)
Primary Dysmenorrhea and Complementary Medicine Ataollahi , M¹; Amir AliAkbari, S*² - Alumnus, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran . (-Lecturer, Dept. of Midwifery, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. Abstract Background and objective: Dysmenorrhea is one of the most common gynecological complaints of women which interfers with daily activities and causes missing work and school. Complementary therapy is a safe , and reliable treatment for primary dysmenorrhea that its effectiveness has been showen in many studies. Considering the prevalence of primary dysmenorrhea and harmful side effects of some synthetic drugs, the present study aims to summarize the effect of complementary medicine on primary dysmenorrhea. Materials and Methods: A search for English and Persian literature published from (000 to (01 was conducted using key words : dysmenorrhea-primary dysmenorrhea ,complementary therpy and nonpharmachologic tetherapy from databases Pubmed, SID, Scirus and Elsevier .A total number of 30 publications were included in the review. Results: Complementary medicine includes the use of dietary supplements, vitamins, aroma therapy, herbal therapy, homeopathy, acupressure, sport and massage and is safe, affordable, and accessible. It has less side effects, acceptability and high tolerability and can replace highly morbid chemical agents. Conclusions: based on the findings of the present research and the high prevalence of dysmenorrhea, further studies on the side effects and benefits of complementary medicine and comparing the influence of complementary medicine with chemical drugs is mandatory. Keywords: primary dysmenorrhea, complementary medicine, herbs, pain reduction. *Corresponding Author: Sedigheh, Amir AliAkbari. Lecturer, Dept. of Midwifery, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: asa_akbari@yahoo.com